Computed tomographic arthrography is a useful adjunct to survey computed tomography and arthroscopic evaluation of the canine shoulder joint. Issue 5 (24th July 2018) - Eivers, Caroline R.; Corzo‐Menéndez, Nuria; Austwick, Sarah H.; Thomson, David G.; Gibson, Sarah M.; Handel, Ian; Schwarz, Tobias
Abstract: The aim of this retrospective, methods comparison study was to assess the diagnostic utility of computed tomographic arthrography in the assessment of various intraarticular shoulder pathologies in dogs in comparison with survey computed tomography (CT), using arthroscopic examination as the reference standard. Computed tomography, computed tomographic arthrography, and arthroscopic findings of 46 scapulohumeral joints of dogs with forelimb lameness were reviewed retrospectively. Predefined sites were assessed for the presence or absence of disease. If a lesion was present, a prespecified pathology was designated. Computed tomographic arthrography was found to be a safe technique which provided a superior diagnostic efficacy relative to survey CT for the assessment of the biceps tendon and biceps tendon sheath (sensitivity 71%, specificity 75%, positive likelihood ratio 2.9, negative likelihood ratio 0.38) and humeral head cartilage (sensitivity 65%, specificity 97%, positive likelihood ratio 19, negative likelihood ratio 0.37). Computed tomography and computed tomographic arthrography provided additional diagnostic information to arthroscopy in regard to osteophytosis, subchondral defects, and joint mice. Computed tomographic arthrography alone was of limited diagnostic value for assessment of the medial and lateral glenohumeral ligaments (sensitivity 13% and 0%, specificity 1% and 78%, positive likelihood ratios unmeasurable and 0, negative likelihood ratios 0.88 and 1.29, respectively) and the subscapularis tendon (sensitivity 14%, specificity 98%, positive likelihood ratio 5.7, negative likelihood ratio 0.88). Computed tomographic arthrography is therefore a useful adjunct to survey CT and arthroscopic evaluation of the canine shoulder joint, however, is not a replacement for these techniques.